Study on Preparation and Properties of High-Strength Nano-Ceramic Coating on the Surface of Steel Structure Connectors - Hui Wang (Advances in Multimedia)
In this paper, the preparation process of high-strength nano-ceramic coating on the surface of steel structure connectors is analyzed. By observing the surface morphology and internal defects of the ceramic coating, this paper analyzes the coating defects in combination with the coating deposition process. Moreover, this paper uses XRD to analyze the phase transition of the ceramic coating before and after spraying and tests the toughness of the coating, the adhesion between the coating and the reinforcement matrix, and the adhesion between the ceramic coating and the concrete. In addition, this paper studies its performance in combination with test research. The test results verify that the high-strength nano-ceramic coating on the surface of the steel structure connector has good performance.